Students’ Perceptions of Kahoot! Use in English Learning at Senior High School in West Sumatra - Nadila Febrina Eka Putri; Siska Siska; Melvina Melvina (Journal of English Language and Education, 2026)
The use of gamification in English language learning has become increasingly significant, particularly through application-based interactive media such as Kahoot! which is considered effective in fostering an enjoyable learning environment and enhancing students’ motivation and engagement. However, studies examining students’ perceptions of Kahoot! implementation at the high school level, especially in West Sumatera, remain limited. This study aims to investigate students’ perceptions of the use of Kahoot! by an English teacher at SMAN 1 Sitiung. A qualitative case study design was employed, involving five twelfth-grade students selected through purposive sampling. Data were collected through structured in-depth interviews and analyzed using an interactive qualitative analysis model focusing on effectiveness, competitiveness, and ease of use. The findings reveal that students hold positive perceptions of Kahoot! as it promotes an enjoyable learning environment, encourages healthy competition, and is easy to use and access both inside and outside the classroom. In conclusion, Kahoot! is an effective gamification tool that supports student engagement and motivation in English learning.